2008
DOI: 10.1109/imcsit.2008.4747348
|View full text |Cite
|
Sign up to set email alerts
|

Estimating time series future optima using a steepest descent methodology as a backtracker

Abstract: Recently it was produced a backtrack technique for the efficient approximation of a time series' future optima. Such an estimation is succeeded based on a selection of sequenced points produced from the repetitive process of the continuous optima finding. Additionally, it is shown that if any time series is treated as an objective function subject to the factors affecting its future values, the use of any optimization technique finally points local optimum and therefore enables accurate prediction making. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In [3] was discussed the similarity between a time series and an objective function; based on this realization the usage of calculus tools-such as the local Lipschitz continuity-was extended to time series analysis, too.…”
Section: The Local Lipschitz Constantmentioning
confidence: 99%
See 4 more Smart Citations
“…In [3] was discussed the similarity between a time series and an objective function; based on this realization the usage of calculus tools-such as the local Lipschitz continuity-was extended to time series analysis, too.…”
Section: The Local Lipschitz Constantmentioning
confidence: 99%
“…Specifically, the indicator is approximated over a time series constructed from deductions of the local estimations of the Lipschitz constant, and results to the usage of the Lipschitz constant as the sole crisis indicator. The research of the local Lipschitz constant was motivated from previous realizations [3], where it was observed that a time series holds functional properties.…”
Section: The Usage Of Local Lipschitz Constant Approximations As a Crisis Indicatormentioning
confidence: 99%
See 3 more Smart Citations